Orthopaedic manipulative physiotherapy in South Africa - M. S. Uys (South African Journal of Physiotherapy, 1996)
To ensure effective patient care, all members of the health team should review professional competency and standards of service provision. A questionnaire was sent to all members of the orthopaedic Manipulative Therapists group (OMTG) to establish their qualification and skills, and the scope of practice of Orthopaedic Manipulative Therapy (OMT) physiotherapists. It included a short self and peer review. The results of this study urge the NEC of the OMTG to address pertinent issues that were raised: post-graduate study, international trends, research, dissemination of knowledge, quality assurance, professional image and prophylactic programmes in a primary health care system.